The role of economic convergence in the capability of the Islamic world - Sayed Mujiburahman Noori; Ahmad Nabi Stanikzai; Gulaqa Anwari (International Journal Of Humanities Education and Social Sciences (IJHESS), 2023)
Achieving positive global development in today's world is possible through convergence. Major global competitors are moving forward by forming unions and agreements based on common interests. This is something that Islamic countries are in desperate need of. The focus of this research is also on the role of economic convergence in enhancing the capabilities of the Islamic world. In this research, a qualitative method has been used using articles, books and also according to detailed information from reliable global sources. The aim is for the Islamic world to reach a level of development through cooperation and solidarity among Islamic countries and by meeting the needs of the Islamic Ummah, freeing themselves from severe economic dependence. The results indicate that the Islamic world can effectively work towards common goals and maximize its economic potential. Islam, with its emphasis on Allah almighty, aims to bring honor and glory to Muslims and enable them to participate in international competition, utilizing their material and spiritual talents and abilities. With cultural, historical, and emotional ties among Muslim nations and the large group of 57 countries that make up the Organization of Islamic Cooperation, representing over one and a half billion people, accounting for nearly 60% of global strategic reserves, there is immense potential for economic convergence if they focus on common development-oriented interests and goals. By doing so, Islamic societies can thrive and make a significant impact in the international arena as a strong economic force